Nanocomposite films based on chia (Salvia hispanica L.) flour seeds incorporating antioxidant chitosan nanoparticles - Morales-Olán, Gema; Moreno-Zarate, Pedro; Ríos-Corripio, María Antonieta; Hernández-Cázares, Aleida Selene; Rojas-López, Marlon; Luna-Suárez, Silvia (Frontiers in Chemistry, 2024)
Chia (Salvia hispanica L.) flour seeds produce films with good barrier properties against water vapor and could be used as food packaging; however, their mechanical properties are poor, which limits their application. The incorporation of nanoparticles into natural polymers is a strategy used to improve the properties of films to increase their applications. Furthermore, nanoparticles can encapsulate antioxidant agents and generate active films. The objective of this study was to evaluate the influence of chia flour (4%–7%), glycerol (15%–25%), and chia extract-loaded chitosan nanoparticles (ChCNp) (0%–0.75%) on the physical, mechanical, barrier, structural and antioxidant properties of chia flour nanocomposite films. Chitosan nanoparticles loaded with antioxidant chia extract were synthesized by ionic gelation and incorporated into the films. The thickness, water vapor permeability, tensile strength, and antioxidant properties of the films were evaluated using a Box-Behnken experimental design. Structural analysis was conducted using the FTIR technique. The results of the ANOVA of the responses were adjusted to second and third order polynomial models obtaining determination coefficients of 0.96–0.99. The water vapor permeability of the films was 3.89 × 10-8–1.68 × 10−7 g mm/Pa s m2, tensile strength was 0.67–3.59 MPa and antioxidant activity was 57.12%–67.84%. The variables presented different effects on the films. Increasing the chia seed flour concentration negatively affected the water vapor permeability but improved the tensile strength and the antioxidant capacity of the films. The increase in glycerol concentration caused the films to become brittle. The nanoparticles had a significant effect on the thickness of the films and improved their mechanical and antioxidant properties. However, they did not show an effect on barrier properties. The results demonstrate that it is possible to obtain nanocomposite films with antioxidant capacity from chia seed flour and with the incorporation of chitosan nanoparticles loaded with antioxidants.